The Influence of Employee Wellness Program Intervention on Job Satisfaction with Perceived Organizational Support as a Mediating Variable on Employees of PT PLN (Persero) UID Sumatera Utara - Anne Setiyani; Zulganef Zulganef (Dinasti Review, 2025)
This study aims to analyze the effect of Employee Wellness Program intervention on job satisfaction among employees of PT PLN (Persero) UID Sumatera Utara, with Perceived Organizational Support as a mediating variable. Using a quantitative approach with SEM analysis, data was collected from 270 employees who participated in the Employee Wellness Program. The results show that the Employee Wellness Program positively affects job satisfaction, with Perceived Organizational Support mediating the relationship effectively. These findings guide PT PLN (Persero) in optimizing employee wellness policies to enhance job satisfaction and organizational performance.